Pengaruh Lingkungan Kerja dan Kompensasi Dana Bantuan Operasional Sekolah terhadap Motivasi Serta Dampaknya Kepada Kinerja Guru Madrasah Aliyah Swasta Perguruan Hidayatul Islamiyah di Kuala Tungkal - Muhammad Said; M. Zahari MS; Fakhrul Rozi Yamali; Fakhrul Rozi Yamali (Universitas Batanghari, 2023)
The research object was all teachers at the PHI Private Islamic School (MAS) in Kuala Tungkal, West Tanjung Jabung Regency. The total population is 40 teachers and all of them are used as samples. The analytical method uses the Path Analysis tool, and tests the hypothesis with the F test and t test. Data processing using SPSS V.22 software. The results of the study show: 1) The working environment conditions are in the good category and compensation, motivation and performance are included in the high category; 2) Work environment and alarms have a direct and indirect effect on motivation. Likewise with simultaneous hypothesis testing and part of the work environment and significant influence on motivation; 3) Work environment and alarms directly and indirectly affect performance. Likewise with simultaneous hypothesis testing and part of the work environment and significant influencers on performance; 4) Motivation has a significant effect on performance; and 5) The work and protective environment through motivation influences the performance of teachers at the PHI Private Madrasah Aliyah in Kuala Tungkal.